“AZUFRASIN”: A NEW YELLOW SEEDED DRY BEAN CULTIVAR FOR THE STATE OF SINALOA - Salinas Pérez, Rafael Atanasio; Rodríguez Cota, Franklin Gerardo; Padilla Valenzuela, Isidoro; Valencia Martínez, Yeny; Acosta Gallegos, Jorge Alberto (Revista Mexicana de Ciencias Agrícolas, 2018)
In the state of Sinaloa, Mexico; the yellow bean of Azufrado-Peruano, Nueva Granada race, which occupies most of the surface area to meet the domestic demand and for exporting to the United States. The development and agronomic characteristics of the new bean variety are described, ‘Azufrasin’; whose use will expand the number of available varieties of this bean in the state. This new variety was developed from crosses between three lines ((Azufrado Pimono-78/Canario-72)//AZPA-5); during the development, the selection was based on tolerance to viral diseases (BCMV and BCMNV), white mold (Sclerotinia sclerotorium) and resistance to rust (Uromyces appendiculatus var. appendiculatus). Azufrasin has a determinate growth habit (Type I), high bearing with plants of 45 cm, 100 days to physiological maturity and a hundred seeds weight varies from 44 to 46 g. Azufrasin shows adaptation in bean-producing areas of northern Sinaloa under irrigated conditions, where it has shown high yield capability and high diseases tolerance during Autumn-Winter cycle, exceeding yield of Azufrado Higuera variety with an average of 339 kg ha-1.
Keywords: Adaptation; agronomic characteristics; disease tolerance